2022
DOI: 10.1111/apa.16315
|View full text |Cite
|
Sign up to set email alerts
|

Former street‐working boys in Iraq highlight the importance of receiving education, training and support from families and other adults

Abstract: Aim This study investigated the perceptions of men who worked on the streets of Iraq when they were children. It looked at the risks they faced, how they developed resilience and what support they feel current working children need. Methods In 2021, semi‐structured interviews were held with 40 men aged 24–33 who used to work on the streets as children. They had attended the Zewa Centre, a drop‐in centre for street‐working children in 2004–2005. Thematic analysis was used to explore the transcribed interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…At both baseline and follow-up, each participant’s medical history was taken by the same person that afterwards conducted the diagnostic interview. At follow-up, but not at baseline, the structured diagnostic interview was followed by questions about their experiences of street work; the results obtained from the latter parts of the interviews have already been published [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…At both baseline and follow-up, each participant’s medical history was taken by the same person that afterwards conducted the diagnostic interview. At follow-up, but not at baseline, the structured diagnostic interview was followed by questions about their experiences of street work; the results obtained from the latter parts of the interviews have already been published [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors identified four themes with several sub-categories. 8 Experiences from street work were positive and negative (Theme 1). As adults, they appreciated the relationship with other streetworking children who were described as supportive, loyal and helpful when in need.…”
Section: Maconachie Et Al Highlight Ilo's Definition Of Child Labour Asmentioning
confidence: 99%
“…In this issue of Acta Paediatrica, Taib and co-authors report on their qualitative study among former street-working boys in Duhok, in the Kurdistan Region of Iraq. 8 As children, aged 8-16 years, they had been engaged in various activities on the streets, for example, selling goods, shining shoes and working as assistants; a few were stealing or begging. Most claimed that they worked because of family needs and pressures.…”
Section: Maconachie Et Al Highlight Ilo's Definition Of Child Labour Asmentioning
confidence: 99%
See 2 more Smart Citations